PENGARUH PENGETAHUAN KEUANGAN DAN PENGALAMAN KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA DI KOTA PALOPO - Nur Wafiq Azizah; Rifqa Ayu Dasila; Sultan (ITB AAS Indonesia Surakarta, 2025)
Financial failure nowadays often occurs among students due to a lack of attention to their financial condition and financial management.Therefore, students as intellectuals at least have good financial knowledge so they can implement good financial behavior. The purpose of this research is to determine the influence of financial knowledge and financial experience on the financial behavior of students in Palopo City. The number of samples in this study was 81 students using a disproportionate cluster random sampling technique. The analysis technique in this research uses multiple linear regression, with validity and reliability test stages, classical assumption test, t test, f test and coefficient of determination test. The research result show that financial knowledge has no influence on financial behavior and financial experience has an influence on financial behavior. Simultaneously, both variables jointly influence financial behavior.